DASAR – DASAR PERPAJAKAN - Annisa Zahrina Dharmawan; Putri Wulandini Sagala, Salwa Hayati Harahap, Silpiah Jahra Nasution (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
Taxation is a vital instrument for the state in collecting revenue to finance public expenditure and support economic development. The basics of taxation include the fundamental concepts that form the framework of the tax system, including types of taxes, collection principles, statutory regulations, and tax administration. Types of taxes such as income tax, value added tax, and land and building tax have different characteristics and imposition mechanisms. The main principles of taxation include fairness, certainty, comfort and efficiency which aim to create a fair and effective tax system. A good understanding of the basics of taxation is very important for all parties involved, including the government, taxpayers and tax professionals, to ensure compliance and optimize state revenues through a transparent and accountable system